Treatment of Advanced or Metastatic Urothelial Cancer - Hilser, Thomas; Darr, Christopher; Bedke, Jens; Ivanyi, Philipp; Klümper, Niklas; Eckstein, Markus; Schlack, Katrin; Grünwald, Viktor (Oncology Research and Treatment, 2025)
Background: Urothelial carcinoma (UC) is a significant global health burden and shows consistent increase in incidence. The treatment landscape for advanced or metastatic urothelial carcinoma (mUC) has evolved, but significant challenges remain to prolong survival. The article is based on the content of the recent guidelines and a selective literature search. Summary: For many years in the past, cisplatin-based chemotherapy was the standard firstline therapy for eligible patients. But chemotherapy alone provides limited long-termbenefit, and a large proportion of patients either progress rapidly or are ineligible for cisplatin due to comorbidities. This demonstrates the medical need and led to the development of immune checkpoint inhibitors and antibody-drug conjugates (ADCs) in the field of mUC treatment. More recently, the introduction of ADCs further enlarged the medical armamentarium in mUC patients and was further explored as combined regimens. The combination of enfortumab vedotin (EV) and pembrolizumab was superior to standard platin-based chemotherapy as did nivolumab plus gemcitabine with cisplatin, which permanently transformed the medical treatment landscape in mUC. Today, EV plus pembrolizumab is the first-line standard in treatment of therapeutic advanced or mUC. New options are also emerging, such as molecular therapies that target the fibroblast growth factor receptor. In the future, targeted therapy could also be used in the perioperative area. Key Message: Today, EV combined with pembrolizumab sets a new standard of care in medical treatment of a/mUC patients. Compared to platinum-based therapy, EV plus pembrolizumab doubled the overall survival probability and reported a median OS of 31.5 months, which is a new hallmark of palliative medical treatment in this disease. This novel therapy in combination with molecular therapies, novel devices, and molecular markers offers a great opportunity for the next step in medical development in localized UC, and its clinical applicability is being investigated in ongoing studies.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Enfortumab vedotion; Erdafitinib; Immune checkpoint inhibitor; Urothelial cancer